2018
DOI: 10.1002/ece3.3820
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isolation, fragmentation, and population bottlenecks on song structure of a Hawaiian honeycreeper

Abstract: Little is known about how important social behaviors such as song vary within and among populations for any of the endemic Hawaiian honeycreepers. Habitat loss and non‐native diseases (e.g., avian malaria) have resulted in isolation and fragmentation of Hawaiian honeycreepers within primarily high elevation forests. In this study, we examined how isolation of Hawai'i ‘amakihi (Chlorodrepanis virens) populations within a fragmented landscape influences acoustic variability in song. In the last decade, small, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It is possible because local population of "native speakers" was numerous all the time of dialect existence. Otherwise, the song diversity declines (Pang-Ching et al, 2018;Paxton et al, 2019), and the number of songs would be incomparably lesser than in other dialects.…”
Section: History Of Dialectmentioning
confidence: 95%
“…It is possible because local population of "native speakers" was numerous all the time of dialect existence. Otherwise, the song diversity declines (Pang-Ching et al, 2018;Paxton et al, 2019), and the number of songs would be incomparably lesser than in other dialects.…”
Section: History Of Dialectmentioning
confidence: 95%
“…Therefore, the alteration of habitat structure can influence both the structure of acoustic signals as well as the reliability of acoustic communication (reviewed in Rabin & Greene, 2002). For example, the songs of Hawai'i 'amakihi birds (Chlorodrepanis virens) in less-complex habitats have more energy at higher frequencies than songs in closed habitats (Pang-Ching et al, 2018). Observational comparisons of black-capped chickadees found that birds in disturbed habitats have reduced signal reliability and can likely hear fewer other males compared to chickadees living in highquality old-growth habitat (Hansen et al, 2005).…”
Section: (A) Communicationmentioning
confidence: 99%
“…If current rates of decline for Kaua‘i honeycreepers continue, multiple extinctions are predicted in the coming decades [31]. Based on field observations of apparent increasing similarity in song among Kaua‘i honeycreeper species, we hypothesized that rapid declines in the density and distribution of Kaua‘i honeycreepers could have resulted in the loss of complexity and diversity within species' present-day songs [33] due to the lower number of individuals from which young birds can learn, resulting in an increase in similarity among species’ present-day songs. We examined acoustic characteristics of songs recorded during three time periods (1970s, early 2000s, present day) for three species of honeycreepers: ‘akeke‘e ( Loxops caeruleirostris ), ‘anianiau ( Magumma parva ) and Kaua‘i ‘amakihi ( Chlorodrepanis stejnegeri ).…”
Section: Introductionmentioning
confidence: 99%
“…If current rates of decline for Kaua'i honeycreepers continue, multiple extinctions are predicted in the coming decades [31]. Based on field observations of apparent increasing similarity in song among Kaua'i honeycreeper species, we hypothesized that rapid declines in the density and distribution of Kaua'i honeycreepers could have resulted in the loss of complexity and diversity within species' present-day songs [33] due to the lower number of individuals from which young birds can royalsocietypublishing.org/journal/rsos R. Soc. open sci.…”
Section: Introductionmentioning
confidence: 99%